The Influence of Shopping Lifestyle and Hedonic Shopping Motivation on Impulse Buying in Bukalapak E-Commerce (Study on Bukalapak Consumers in Bandar Lampung) - Novriady Nurtanio, Ilham; Bursan, Rinaldi; Wiryawan, Driya; Listiana, Indah; Maruf, Chasan (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
At present the advancement of data innovation is endlessly quick, remembering for Indonesia itself. Information technology in the world, even in Indonesia has been widely used as a tool for human life activities in various aspects of life, including business activities. The current e-commerce phenomenon is increasingly causing the rise of various online stores in Indonesia. One of the providers of online business digital platforms is Bukalapak. This study was conducted to determine whether there is a significant effect given by the variabel Shopping Lifestyle and Hedonic Shopping Motivation as an independent variable on the Impulse Buying variable as the dependent variable (Study on Bukalapak Consumers in Bandar Lampung). The data used in this study is primary data, which was obtained from the results of respondents answers which were collected with the help of a questionnaire. The number of samples in this study were 108 respondents. The sampling method uses a non-probability sampling technique, which is a technique to determine the sample with certain considerations. The analytical method used in this research is validity test, reliability test, analysis multiple liniear regression, and hypothesis testing, namely t test and coefficient of determnination (R2), with the help of the IBM SPSS 26 application program for windows. The results of this study indicate that the Shopping Lifestyle variable has a significant effect on the Impulse Buying variable as evidenced by the t-count values of 3.009 > from the t-table value of 1.98304 with a significance level of 0,003 < 0,05. The the Hedonic Shopping Motivation variable also has a significant effect on the Impulse Buying variable as evidenced by the t-count value of 2.684 > from the t-table value of 1.98304 with a significance level of 0,008 < 0.05. Meanwhile, in this study, the independent variable was able to explain the dependent variable by 47,3% while the rest was influenced by other variables outside the variable of this study.